Mechanisms of immune evasion and current status of checkpoint inhibitors in non‐small cell lung cancer. (15th July 2016) - Qin, Angel; Coffey, David G.; Warren, Edus H.; Ramnath, Nithya
Abstract: In the past several years, immunotherapy has emerged as a viable treatment option for patients with advanced non‐small cell lung cancer (NSCLC) without actionable driver mutations that have progressed on standard chemotherapy. We are also beginning to understand the methods of immune evasion employed by NSCLC which likely contribute to the 20% response rate to immunotherapy. It is also yet unclear what tumor or patient factors predict response to immunotherapy. The objectives of this review are (1) review the immunogenicity of NSCLC (2) describe the mechanisms of immune evasion (3) summarize efforts to target the anti‐program death‐1 (PD‐1) and anti‐program death‐ligand 1(PD‐L1) pathway (4) outline determinants of response to PD‐1/PD‐L1 therapy and (5) discuss potential future areas for research. Abstract : Immune checkpoint inhibitors have become an important class of drugs to treat advanced non‐small cell lung cancer (NSCLC), but only about 20% of patients respond to treatment. We discuss the mechanisms of immune evasion employed by NSCLC and potential molecular predictors of response to checkpoint inhibition.